2015
DOI: 10.1186/s12879-015-1030-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment challenges for urogenital and anorectal Chlamydia trachomatis

Abstract: While true antimicrobial resistance to Chlamydia trachomatis is a rare occurrence, repeat chlamydia infections continue to be reported following treatment with a single 1 g dose of azithromycin or week long doxycycline – with considerable more concern about azithromycin treatment failure. While most repeat positive cases are likely to be reinfections, emerging evidence indicates treatment failure may play a role. Current data suggests that there may are differences in the efficacy of the drugs between rectal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 66 publications
1
57
0
2
Order By: Relevance
“…Regardless of these limitations, our findings are consistent with published observational data which suggest that doxycycline may be up to 20% more effective than azithromycin for rectal chlamydia . It is also biologically plausible that azithromycin may not be as effective for rectal chlamydia as urogenital infections for several reasons, including the possibility that the immune response to infection is different in the rectal mucosa, which may impact azithromycin being delivered to the site of infection; this does not apply to doxycycline .…”
Section: Discussionsupporting
confidence: 87%
“…Regardless of these limitations, our findings are consistent with published observational data which suggest that doxycycline may be up to 20% more effective than azithromycin for rectal chlamydia . It is also biologically plausible that azithromycin may not be as effective for rectal chlamydia as urogenital infections for several reasons, including the possibility that the immune response to infection is different in the rectal mucosa, which may impact azithromycin being delivered to the site of infection; this does not apply to doxycycline .…”
Section: Discussionsupporting
confidence: 87%
“…This type of high-resolution data can be used to understand the genetic diversity of current C. trachomatis strains causing genital and rectal infections and provide a robust molecular epidemiologic approach to advance our understanding of geo-sexual networks, outbreaks of colorectal infections among women and men who have sex with men, and the role of these strains in morbidity. The bioinformatic pipeline can further be used to potentially identify novel markers for typing C. trachomatis and to examine the microbiome to determine the role it plays in susceptibility, transmission and clearance of rectal C. trachomatis infections, especially given the need for a longer duration of therapy compared to most uncomplicated urogenital infections 80,81 . Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…cycline was 95 % in relation to azithromycin (77 %) (26). Later, Kong and co-authors showed even less efficiency with doxycycline in relation to azithromycin than to the earlier study (27,28). A metanalysis by Kong showed a minimal difference of 2-6 % with doxycycline in relation to azithromycin.…”
Section: Discussionmentioning
confidence: 88%